(untitled) (Scientific journal of the Fergana State University, 2026)
The aim of this study was to investigate nickel-containing catalysts used for reducing greenhouse gases and the carbonate conversion of methane. The objects of the study were polyoxide catalysts with the compositions 4NiO∙ZrO2/5Al2O3, 4NiO∙TiO2/5Al2O3 and 3NiO∙TiO2∙ZrO2/5Al2O3, synthesized via sol-gel technology and solution-combustion synthesis based on d-element oxides. The influence of temperature on the process of syngas production through carbonate conversion of methane was examined. The development of cost-effective and highly efficient catalytic systems for the carbonate conversion of methane is crucial for the sustainable production of hydrogen (H₂). To ensure the process is efficient, we studied the application of TiO2∙ZrO2 as a promoter in Ni-containing catalysts, as well as the use of aluminum oxide (Al₂O₃) as a support. Addition of TiO2∙ZrO2 as a promoter resulted in increased basicity and a significant increase in the yield of synthesis gas. Effect of temperature on the carbonate conversion reaction process and concentration of the main conversion products using 4NiO∙ZrO2/5Al2O3, catalyst: at a temperature of 850°C, methane conversion was 87%, and carbon dioxide – 77.1%, when using 4NiO∙TiO2/5Al2O3 catalyst, methane conversion was 71.3%, and carbon dioxide – 65.2%, and when using 3NiO∙TiO2∙ZrO2/5Al2O3 catalyst, methane conversion was 92.1%, and carbon dioxide – 87%.